Molecular pathways affecting reproductive efficiency in seasonal breeders: prospects and implications for improving fertility in donkeys - Akhtar, Muhammad Faheem; Ali, Shahzad; Hassan, Faizul; Changfa, Wang (Frontiers in Veterinary Science, 2025)
Intense neuroendocrine and molecular pathways with environmental sensitivity maintain reproductive efficiency in seasonal breeders, together with donkeys. The hypothalamic–pituitary-gonadal (HPG) axis functions as a primary controller through modifying gonadotropin-releasing hormone (GnRH) secretion that depends on melatonin levels, which induces photoperiodic instructions to the system. The activation of HPG axis is triggered by decreasing melatonin levels during long-day seasons, yet sustained high levels of melatonin during short-day seasons cause its suppression. The reproductive pulsatility of GnRH depends on kisspeptin-neurokinin B-dynorphin (KNDy) neurons, which are controlled by melatonin through activity regulation to produce seasonal reproductive suppression. Reproductive ability depends on metabolic signaling, which connects nutrient availability to gonadal functions to maintain fertility during optimum nutritional status. Studies have demonstrated that oxidative stress is a primary disruptor of reproductive functions as it produces gonadal cell damage while stopping steroid synthesis and increasing cell death. Endocrine-disrupting chemicals (EDCs) cause additional reproductive problems through interfering with steroidogenic enzymes, which results in hormonal imbalance and infertility. Prolactin works in association with gonadotropins and metabolic pathways to control reproductive adaptations under seasonal variation. Understanding of molecular mechanisms is essential for increasing reproductive success among donkeys and other seasonal breeders in general. The breeding programs might benefit from solutions such as photoperiod manipulation and melatonin treatments, together with nutritional supplementation and antioxidant therapies. The review focuses on seasonal reproductive processes, endocrinology, assisted reproductive technologies (ARTs), and peculiarities of anatomy and behavior. Discoveries in sperm vitrification, testicular immunology, metabolic endocrinology, and follicular dynamics give important clues to fertility manipulation in this species and suggest interventions to be pursued to enhance fertility outcomes and conservation approaches.